Optimum Control of Grid-Connected Solar Power System Under Asymmetrical Voltage Drop - Van Binh Nguyen (International Journal of Renewable Energy Development, 2022)
Solar power systems are now gradually dominating in providing clean, environmentally friendly energy and human health. In areas with a large share of solar power, grid connection control plays a key role in ensuring operational quality and stability, especially in the event of a grid failure. In case of asymmetrical voltage drop, the control system needs to maintain operation and create a function to assist in restoring the power grid. This study proposes a method to control the solar power system in the condition of asymmetric grid voltage drop based on the method of controlling symmetrical components. Controllers for each of the forward and inverse components are built to limit the effects of failures. The optimal control parameter calculation method is also proposed to improve the overall quality and minimize the undesired variation of the electromagnetic quantities. The simulation and experimental results are verified to evaluate the effectiveness of the grid-connected control method in converting DC power to three-phase power.